Improvement of methods and devices for organic impurities control in the coolant at TPP and CHP - Vladimir N. Shcherbakov; Maxim S. Poleshkin; Vladimir I. Antonenko (Advanced Engineering Research)
Introduction. Issues of increasing the reliability of investigating the coolant’s organic impurities behavior and the operational control of their concentrations at TPPs and CHPs are considered. Possible causes of the organics occurrence in the boiler feedwater and in the steam of the power plants are analyzed. The behavior of typical impurities in the liquid and vapor phases at high temperatures is studied. Materials and Methods. The analysis of the existing methods and devices for the organic impurities control in the coolant of the TPP and CHP circuits is conducted. Research Results. Taking into account the advantages and disadvantages of the existing techniques and monitoring devices, methods of their improvement are proposed. When monitoring the thermolysis process of the potentially acidic organic impurities in the liquid and vapor phases, it is recommended to use the installation of the All-Russian Technological Institute improved by the authors. In this case, the conductometric control of the thermolysis process in the vapor phase at different temperatures on the concurrent boilers should be carried out according to the readings of the conductometric cooled sensor placed in the controlled steam. A technique for the simultaneous measurement of the specific electric conductivity of water and steam condensate in the coolable conductivity sensor is proposed to simplify the study of the transition of organic impurities from boiling water to saturated steam. All this will allow obtaining the objective information about the organic impurities behavior in the water-steam circuit of the power units, the thermolysis process, and the sources of hazardous impurities flow into the boiler. Besides, taking into account the results of this work, the researchability of the behavior of potentially acidic substances and monitoring of their content in water and steam can be enhanced. Discussion and Conclusions. The advanced control devices can be used as a supplement to the existing ones for joint operation in the chemical and technological monitoring systems of the power plants. A method for improving the operating modes control systems of the evaporator plants under the thermal treatment of water from organic impurities, mainly to reduce the content of potentially acidic substances in steam and condensate of the plants, is proposed. For this purpose, it is recommended to use the control sensors previously developed by the authors.